(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Polycyclic aromatic hydrocarbons (PAHs) are contaminants of interest due to their known toxic effects. PAHs may interfere with physiological and biochemical activities of soil organisms like Lumbricus terrestris. PAHs metabolites have been employed in the assessment of external PAHs exposure and metabolic activation. Thus, this study investigates PAHs metabolites and antioxidant stress markers in Lumbricus terrestris which is a recognized bioindicator of environmental pollution. Samples of Lumbricus terrestris were collected from four sampling sites of Emeyal, Imiringi, Elebele and Otuasega around Kolo Creek, Niger Delta, Nigeria. The PAH metabolites and other biochemical parameters were determined using standard laboratory procedures. The results showed that the concentrations of the âˆ‘5-OH PAHs in the Lumbricus terrestris ranged from 0.55 to 16.6 mg/kg. On the average, the concentrations of the PAHs metabolites followed the order: 9-OH Fluorene (Flu) > 2-OH Napthalene (Nap) > 1-OH Pyrene (Pyr) > 3-OH Phenathrene (Phen) > 3-OH Benzo(a)pyrene (Bap). The antioxidative stress markers which comprises of superoxide dismutase, catalase, glutathione peroxidise and glutathione s-transferase activities and concentrations of malondialdehyde and reduced glutathione including the activities of acetylcholinesterase and lactate dehydrogenase in the Lumbricus terrestris varied significantly among the sampling sites. The data obtained from this study suggests that Lumbricus terrestris were exposed to PAHs and changes in oxidative stress markers confirm PAHs in the study area. Thus, PAH metabolites and oxidative stress markers in Lumbricus terrestris could be employed as biomarkers for exposure to polycyclic aromatic hydrocarbon and be effectively employed in the biological monitoring of PAHs.